The moderating effect of electronic strategy (e-strategy) on the relationship between perceived usefullness and the intention to adopt online banking in Malaysia - Abdullah, Shahmir Sivaraj; Abdullah, Haim Hilman; Ramanchandram, Rajoo; Gorundutse, Abdullahi Hassan; Yunus, Nek Kamal Yeop (The Academy of Business and Retail Management (ABRM), 2019)
Strategy is an important element in enhancing management competitiveness which directly influences firm performance. Therefore, contemporary business environments which are driven by technology require urgent and sustained attention by firms seeking to enhance their competitiveness. Simply put, technology is the tool through which a firm’s strategy is achieved. Online banking is an example of a technology driven business environment. It is therefore important for the banks who offer this service to understand that the strategy they adopt influences the uptake of the service being offered. The level of adoption of online banking is an indication of the success of the strategy that has been adopted by banks. Consumer perception of the service has a strong influence on its actual usage. This study has used the perceived usefulness (PU) and behavioural intention to adopt (ADO) construct from the technology adoption model and the e-strategy construct to study online banking adoption in Malaysia. The moderation effect of e-strategy on the relationship between PU and ADO was examined. To achieve this, a random sampling of urban residents in the cities Ipoh, Georgetown, Alor Setar and Kangar in Malaysia was used. A total of 2560 questionnaires were distributed but only 360 usable questionnaires were received. The analysis was conducted by using SPSS 24 and Hayes SPSS process macro. From the analysis that was conducted it was found that e-strategy had a positively significant moderating effect on the perceived usefulness of adopting online banking by the consumer. The study found that e-strategy had a stronger effect on PU when applied effectively by banks. The study therefore confirms the hypothesis that the element of strategy influences online banking adoption rates in Malaysia.